The 4-out\1-in motion offense - Adras, Mike (Coaches choice video, 2002)
The 4-out/1-in motion offense explains and show how to help your players read defenses, set effective screens, and create good spacing within the motion. Featuring extensive breakdown drills and game footage, the video discusses why this offense is especially effective for quick teams.